Effectiveness of Immigration Law Enforcement in the Review of the Implementation of Immigration Administrative Actions and Criminal Procedure (Case Study: Class I Special Immigration Office TPI Semarang) - Machmudi, Machmudi; Arifullah, Achmad (UNISSULA Semarang, 2025)
The purpose of this research is to examine and analyze the effectiveness of immigration law enforcement in the implementation of administrative and penal measures against immigration violations at the Class I Special Immigration Office TPI Semarang; as well as to identify the inhibiting factors affecting the effectiveness of immigration law enforcement, both in terms of administrative and penal aspects, and to propose possible solutions. This research employs an empirical juridical approach, combining the study of legal literature (secondary data) and primary data obtained through direct interviews with immigration officials. The research is descriptive-analytical in nature, as it seeks to describe the implementation and obstacles of immigration law enforcement, which are then analyzed juridically and concluded. The results of the research show that the implementation of administrative immigration actions at the Class I Special Immigration Office TPI Semarang has been effective, as evidenced by the consistent enforcement of deportation, deterrence, revocation of stay permits, and administrative fines in a timely and appropriate manner. Penal enforcement for serious violations has also been carried out up to the prosecution stage in court, as in the case of a Nigerian national who misused a visit visa for illegal trade activities. However, the effectiveness of immigration law enforcement is still hampered by several factors, including limited detention facilities, a shortage of competent human resources, budget constraints, weak inter-agency coordination, and low legal awareness among the public. These challenges affect the achievement of both legal effectiveness and legal certainty in the enforcement of immigration law. Therefore, strengthening institutional capacity, enhancing officer competence, providing adequate supporting facilities, and optimizing inter-agency coordination are required as solutions to improve effectiveness and ensure legal certainty in immigration law enforcement.